Principal’s Strategy in Improving Teacher Performance - Nel Vaiza; Jamilus Jamilus (IAIN Batusangkar, 2022)
One of the factors that influence teacher performance is the principal as a school leader. This study aims to analyze the principal's strategy in improving performance. In order to increase teacher performance, a research was conducted on the principal's strategy in improving teacher performance at SMP Negeri 11 Sijunjung.. The methodology used in this research is descriptive qualitative with the type of literature study. Principals and teachers at SMP Negeri 11 Sijunjung were the samples in this study. The research instruments are interviews, observation and documentation. With the research, it can be conveyed that the principal's strategy in improving teacher performance at SMP Negeri 11 can be pursued by maximizing interpersonal communication, strict teacher recruitment, placing teachers in positions that are in accordance with competence both as supervisors and coaches, providing motivation to teachers, conducting training for teachers, conducting supervision and supervision, fostering teacher performance, establishing cooperative relationships with teachers and carrying out disciplinary supervision